Study on potential coconut fiber as shock absorbing product - Nur Nadia, Binti Hamri (Universiti Malaysia Sarawak (UNIMAS), 2017)
Coconut fiber is extracted from the coconut husk which has potential to create shock absorbing product. In this study, natural fibers (coconut fiber) is used in the manufacturing of composite material which is cheap and environmental friendly. Natural fiber was used to replace the existing synthetic fibers such as rubber, neoprene, silicone others elastic polymer. The value of coconut fibers used which are mixed with Urea-Formaldehyde (UF) in the different ratio have been investigated to study the shock ability. There are 3 types of specimens fabricated based on prescribed percentage which is set 10% UF with 90% of coconut fibers (Specimen A), 15% UF with 85% of coconut fibers (Specimen B) and 20% UF with 80% of coconut fibers (Specimen C). The fabrication was done using hot press machine for 15 minutes at the same temperature of 120ºC for the all sample. The objective of the study is to study the potential of coconut fibers as a shock absorbing product. The ability of coconut fibers was evaluated by their mechanical properties on the fiberboard and drop weight impact testing based on ASTM D7136. Experimental results showed the ability of fiberboard to absorb the shock in different samples of ratio.